New Mechanisms of Tumor-Associated Macrophages on Promoting Tumor Progression: Recent Research Advances and Potential Targets for Tumor Immunotherapy. (16th November 2016) - Guo, Qiujun; Jin, Zhichao; Yuan, Yuan; Liu, Rui; Xu, Tao; Wei, Huamin; Xu, Xinyao; He, Shulin; Chen, Shuntai; Shi, Zhan; Hou, Wei; Hua, Baojin
Abstract : The majority of basic and clinical studies have shown a protumor function of tumor-associated macrophages (TAMs), which represent a large proportion of matrix cells. TAMs promote tumorigenesis, and their number is related to the malignancy degree and poor prognosis of many kinds of tumors. Macrophage plasticity makes it possible to change the tumor microenvironment and remodel antitumor immunity during cancer immunotherapy. Increasing numbers of studies have revealed the effects of TAMs on the tumor microenvironment, for example, via promotion of tumor growth and tumorigenesis and through an increase in the number of cancer stem cells or via facilitation of angiogenesis, lymphangiogenesis, and metastasis. Investigators also proposed tumor-immunological treatments targeting TAMs by inhibiting TAM recruitment and differentiation, by regulating TAM polarization, and by blocking factors and pathways associated with the protumor function of TAMs. This comprehensive review presents recent research on TAMs in relation to prediction of poor outcomes, remodeling of the tumor immune microenvironment, and immunological targeted therapies.